BCAA metabolism in cancer progression and therapy resistance: The balance between fuel and cell signaling - Zhou, Yi; Kou, Jiahui; Li, Wenjin; Wang, Yuyao; Su, Xingxing; Zhang, Hongguang (Frontiers in Pharmacology, 2025)
Branched-chain amino acids (BCAAs), including leucine, isoleucine, and valine, play a crucial role in cellular metabolism and signaling. Recent studies have demonstrated that BCAA metabolic reprogramming is a key driver of tumor progression and treatment resistance in various cancers. BCAA metabolism supports cancer cell growth, survival, and proliferation by modulating pathways such as mTOR signaling and oxidative stress responses. By promoting immunosuppressive conditions and increasing the survival rate of cancer stem cells (CSCs), BCAAs contribute to immune evasion and resistance to therapies such as chemotherapy and immune checkpoint inhibitors. This article explores the different metabolic reprogramming patterns of BCAAs in various tumors and introduces BCAA-related metabolic targets for overcoming tumor resistance, offering new directions for precision cancer treatment, reducing resistance, and improving patient outcomes.